Physicochemical Characteristics for Fen (n = 2–10) Cluster by Density Functional Theory - Yamina Benkrima; Djamel Belfennache; Radhia Yekhlef; Mohammed Elbar Soudani; Abdelkader Souiga; Yahia Achour (East European Journal of Physics, 2023)
The In this work, we present a theoretical study on the equilibrium geometry and the energetic, electronic and magnetic properties of Fen (n = 2–10) based on the use of density functional theory (DFT). The results are obtained using Both Generalized Gradient Approximation according to the scheme described by Perdew-Burke-Ernzerhof (GGA-PBE). More stable structures obtained compared to other isomers have not been previously found. It is shown by the results calculated as the calculated fragmentation energy, and the second-order energy difference that Fen (n = 7,8,9) clusters are more stable than the other cluster sizes. The calculated magnetic properties of the most stable clusters display varying magnetic torque between values 3.00 μB and 3.35 μB, except for the Fe10 cluster, which takes the upper value 3.38 μB. These results are very important for experimental experts who are active in designing new nanocatalysis systems in the physical and chemical fields.